Two-stage Frequency Regulation Method for Energy Storage Coordinated with Thermal Power Unit Based on Weight Coefficient Correction - Yibin WANG; Feixiong CHEN; Zhenguo SHAO; Shuling ZHANG; Weijun ZHANG; Zhicheng LI (Zhongguo dianli)
With the large-scale uncertain renewable energy connected to the grid, the frequency characteristics of the power grid are increasingly complex. Plagued by long response times and the inability to accurately track frequency regulation commands, traditional thermal power units call for urgent improvement in the performance of its participation in frequency regulation of automatic generation control (AGC) of thermal power by use of energy storage. Therefore, firstly, the mathematical model of frequency regulation performance index is established according to frequency regulation assessment rules. Besides, considering the output characteristics of the energy storage system, combined with the improved analytic hierarchy process to correct the weight coefficient of the frequency regulation sub index, the first-stage optimization model aiming at the optimal AGC performance is constructed. On this basis, in order to reduce the limit crossing and storage depth charging & discharging cases at the state of charge (SOC), the second-stage optimization model is constructed in order to minimize the SOC deviation. The simulation verification shows that the two-stage frequency regulation method proposed in this paper can improve the frequency regulation performance and benefits of the system of energy storage coordinated with thermal power unit, while reducing the energy storage in-depth charging & discharging cases and working life loss, thus improving the sustainability of frequency regulation auxiliary service of energy storage.